2006
DOI: 10.1051/gse:2005037
|View full text |Cite
|
Sign up to set email alerts
|

A note on QTL detecting for censored traits

Abstract: -Most existing statistical methods for mapping quantitative trait loci (QTL) assume that the phenotype follows a normal distribution and that it is fully observed. However, some phenotypes have skewed distributions and may be censored. This note proposes a simple and efficient approach to QTL detecting for censored traits with the Cox PH model without estimating the baseline hazard function which is "nuisance". QTL detecting / censored trait / interval mapping

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The effects of saponins on in vitro rumen fermentation and the microbial composition are influenced by diet composition (Patra and Yu, 2015). Growing cattle need fiber for rumen development, and soybean hulls and alfalfa hay are two fiber sources that are widely used in cattle production (Richards et al, 2006; Jahani-Moghadam et al, 2015). In this study, we hypothesized that the effects of tea saponins on the rumen microbiota might be influenced by the dietary fiber source and that an interaction between the rumen microbiota and rumen metabolites exists, which would demonstrate a regulatory role of saponins on rumen metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of saponins on in vitro rumen fermentation and the microbial composition are influenced by diet composition (Patra and Yu, 2015). Growing cattle need fiber for rumen development, and soybean hulls and alfalfa hay are two fiber sources that are widely used in cattle production (Richards et al, 2006; Jahani-Moghadam et al, 2015). In this study, we hypothesized that the effects of tea saponins on the rumen microbiota might be influenced by the dietary fiber source and that an interaction between the rumen microbiota and rumen metabolites exists, which would demonstrate a regulatory role of saponins on rumen metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…While the purpose of candidate gene studies is to confirm a biological hypothesis, the aim of GWAS is to uncover novel genes that were not known before to be associated with a given biomarker. Although the issue of dealing with censored data in these contexts has been extensively investigated in the last decade (Epstein et al., ; Diao et al., ; Diao and Lin, ; Fang, ; Li et al., ), the omission of ND values from the analyses is still common although it has been demonstrated that this may lead to biased estimates (Schafer, ; Little and Rubin, ), particularly when the proportion of ND values is above 10% (Lubin et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…
The high temperature and humid weathers coupled with low wind speed can induce heat stress in animal, resulting in reduced growth performance, compromised health status, or even death (Mader, Davis, & Brown-Brandl, 2006). Heat stress is known to disturb metabolic and physiological processes required for optimal cattle productivity, as well as cattle immunity (Collier, Collier, Rhoads, & Baumgard, 2008;Rhoads et al, 2009;West, 2003).
…”
mentioning
confidence: 99%